An Analysis of Students’ Ability in Summarizing Reading Passage in Critical Reading Class - Dwi Chayani; Fitrawati Fitrawati (Journal of English Language Teaching, 2020)
This research aimed to find out the ability of English Department 2017 academic year in summarizing a reading passage in Critical Reading class. This research is descriptive quantitative research. The sample of this research is 27 students selected using cluster random sampling. The instruments used in this research were summary writing test. Students were given a reading passage, entitled "Euthanasia" consisting of 5 paragraphs with 671 words. Students were asked to read the text, and then write a summary. Based on data analysis, it was found that the students' ability in summarizing a reading passage was average. It is proved by all students only able to get scores between 55-79%. This is because as many as 24 (89% of 27 students) students had difficulty in the vocabulary and paraphrasing. They have limited vocabularies. Then, as many as 17 (60% of 27 students) students had difficulty with grammar. It is because they tend to write sentences in incorrect structure. Last, as many as 15 (55% of 27 students) had difficulty to determine the main idea.